Elite education, mass education, and the transition to modern growth - Holger Strulik; Katharina Werner (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2014)
For most of human history there existed a well-educated and innovative elite whereas mass education, market R&D, and high growth are phenomena of the modern period. In order to explain these phenomena we propose an innovation-driven growth model for the very long run in which the individual-specific return to education is conceptualized as an compound of cognitive ability and family background. This allows us to establish a locally stable steady state at which family background determines whether an individual experiences education and a locally stable steady state at which education is determined by cognitive ability. Compulsory schooling can move society from elite education to mass education. An interaction between education and life expectancy explains why the education period gets longer with ongoing economic development. Embedding this household behavior into a macro-economy we can explain different paths to modern growth: According to the Prussian way, compulsory education is implemented first and triggers later on the onset of market R&D and modern growth. According to the British way, market R&D and the take off to growth is initiated without mass education, which is triggered later by technical progress and economic development.
Keywords: I24; J24; O30; O40; 330; long-run growth; elite education; compulsory education; longevity; R&D